Infection rates for open distal phalangeal fractures treated with Kirschner wire: a UK regional hand centre experience - Shaharan, S; Bage, T; Wright, J; Smock, E; Pearl, R (World Scientific Publishing, 2021)
Background: Phalangeal fractures are common in hand injuries which: comprising of 23% of all hand and forearm fractures. The current consensus is that focus of treatment should be on prompt irrigation and debridement to reduce infection risk. These infections are significant as they can lead to serious sequelae including osteomyelitis. The aim of this study was to determine the incidence of infection amongst patients with open fracture of distal phalanx who had been treated with K-wire fixation and the timing of their operative management compared to the UK national guideline. Methods: We performed a retrospective case-note analysis of the patients treated for open distal phalangeal fractures at a regional hands centre over the period of 12 months, and compared with the national guidelines. Data collected included patient demographics, mechanism of injury, length of time taken from injury to first washout, length of time K-wire remains in situ, and infection rate. Results: Half of the patients (n = 19) met the guideline and were treated with washout within the first 24 hours. Infection rates in this group was 11%. This compared with 26% in those patients that did not receive washout within 24 hours. Conclusions: This study demonstrates the difficulty in always meeting national guidelines and suggests key reasons for this. The authors propose a set of local, easily-achieved interventions to raise awareness and compliance with the national guidelines and reduce infection. Furthermore, it highlights the importance of carefully selecting cases that required percutaneous K-wire fixation.